Status of Perinatal Mortality in Karnali Academy of Health Sciences, Jumla Nepal - Sindan, Namrata; Shrestha, Sandeep; Acharya, Bishnu Dutta; Rai, Purnima; Kayastha, Nirajana; Bhandari, Adheesh; Sindan, Namita (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Perinatal mortality rate is sensitive indicator of quality of obstetric and pediatric health services. It also helps us to evaluate efficiency of health care provided by a particular hospital. The aim of this study was to evaluate the cause of perinatal death in a tertiary care medical centre, which may help to reduce the incidence of perinatal death and improve the quality of care. Methods: The two-year retrospective study of perinatal deaths was done at Karnali Academy of Health Sciences (KAHS), Jumla from March 2017 to April 2019. Data was collected from monthly perinatal audit and annual mortality reviews. Registers in the maternity ward, sick Neonate Care Unit, and files of dead newborns kept in the record section of the hospital were studied and reviewed. Results: A total of 1354 deliveries were conducted in the 24 months period at KAHS with perinatal mortality rate of 36.08 per 1000 total birth and early neonatal death rate of 12.8 per 1000 live birth. The Perinatal mortality was higher in low birth weight and premature baby. The cause of stillbirth and early Neonatal death were identified. Most of the early neonatal death was due to Prematurity (41.17%) followed by Birth Asphyxia and Neonatal Sepsis. Conclusion: Prematurity and its related complication were the most common cause of early neonatal death followed by birth Asphyxia and Neonatal Sepsis. There is need to improve antenatal, early identification of high-risk pregnancy as well as Neonatal Intensive Care Unit (NICU) to further reduce deaths due to prematurity and birth asphyxia.